Effectiveness of permanent supportive housing and income assistance interventions for homeless individuals in high-income countries: a systematic review. (June 2020) - Aubry, Tim; Bloch, Gary; Brcic, Vanessa; Saad, Ammar; Magwood, Olivia; Abdalla, Tasnim; Alkhateeb, Qasem; Xie, Edward; Mathew, Christine; Hannigan, Terry; Costello, Chris; Thavorn, Kednapa; et al.
Summary: Background: Permanent supportive housing and income assistance are valuable interventions for homeless individuals. Homelessness can reduce physical and social wellbeing, presenting public health risks for infectious diseases, disability, and death. We did a systematic review, meta-analysis, and narrative synthesis to investigate the effectiveness and cost-effectiveness of permanent supportive housing and income interventions on the health and social wellbeing of individuals who are homeless in high-income countries. Methods: We searched MEDLINE, Embase, CINAHL, PsycINFO, Epistemonikos, NIHR-HTA, NHS EED, DARE, and the Cochrane Central Register of Controlled Trials from database inception to Feb 10, 2020, for studies on permanent supportive housing and income interventions for homeless populations. We included only randomised controlled trials, quasi-experimental studies, and cost-effectiveness studies from high-income countries that reported at least one outcome of interest (housing stability, mental health, quality of life, substance use, hospital admission, earned income, or employment). We screened studies using a standardised data collection form and pooled data from published studies. We synthesised results using random effects meta-analysis and narrative synthesis. We assessed certainty of the evidence using the Grading of Recommendations Assessment, Development, and Evaluation approach. Findings: Our search identified 15 908 citations, of which 72 articles were included for analysis (15 studies on permanent supportive housing across 41 publications, ten studies on income interventions across 15 publications, and 21 publications on cost or cost-effectiveness). Permanent supportive housing interventions increased long-term (6 year) housing stability for participants with moderate support needs (one study; rate ratio [RR] 1·13 [95% CI 1·01–1·26]) and high support needs (RR 1·42 [1·19–1·69]) when compared with usual care. Permanent supportive housing had no measurable effect on the severity of psychiatric symptoms (ten studies), substance use (nine studies), income (two studies), or employment outcomes (one study) when compared with usual social services. Income interventions, particularly housing subsidies with case management, showed long-term improvements in the number of days stably housed (one study; mean difference at 3 years between intervention and usual services 8·58 days; p<0·004), whereas the effects on mental health and employment outcomes were unclear. Interpretation: Permanent supportive housing and income assistance interventions were effective in reducing homelessness and achieving housing stability. Future research should focus on the long-term effects of housing and income interventions on physical and mental health, substance use, and quality-of-life outcomes. Funding: Inner City Health Associates.